2010
DOI: 10.1055/s-0030-1267160
|View full text |Cite
|
Sign up to set email alerts
|

Creatine Activates Airway Epithelium in Asthma

Abstract: TAirway epithelium plays important roles in the pathophysiology of asthma. Creatine supplementation (Cr) was shown to increase asthma features in a murine model of allergic asthma; however, the role of the airway epithelium in this infiammatory response is not known. BALB/c mice were divided into control, creatine supplementation, ovalbumin-sensitized (OVA) and OVA plus creatine supplementation groups. OVA sensitization occurred on days 0, 14, 28 and 42, and ovalbumin challenge from days 21-53. Cr was also giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 25 publications
0
29
0
2
Order By: Relevance
“…Cr supplementation became a popular ergogenic aid to increase muscle performance, 12 with more than 2,500 metric tons used in 2000. 33 Although Cr displays several beneficial therapeutic effects, 2,[12][13][14][15][16]20,21,34 other studies have also found that Cr supplementation does not have a beneficial effect on the respiratory system during respiratory diseases. 15,[35][36][37] This study, however, indicates that Cr supplementation presents beneficial effects after lung I/R injury, including improvements in lung mechanics and inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cr supplementation became a popular ergogenic aid to increase muscle performance, 12 with more than 2,500 metric tons used in 2000. 33 Although Cr displays several beneficial therapeutic effects, 2,[12][13][14][15][16]20,21,34 other studies have also found that Cr supplementation does not have a beneficial effect on the respiratory system during respiratory diseases. 15,[35][36][37] This study, however, indicates that Cr supplementation presents beneficial effects after lung I/R injury, including improvements in lung mechanics and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…16,32 The measurements were performed in 5 entire pulmonary artery walls and in 5 entire bronchial walls of each rat at original magnification Â400 in a blinded fashion. The results were expressed as percentage of positive-stained area in relation to the total area of the artery wall and of the bronchial epithelium.…”
Section: Quantitative Analysis By Image Analysis Of Immunohistochemismentioning
confidence: 99%
See 2 more Smart Citations
“…Os animais doadores receberam creatina (Sigma®, 0,5g/kg/dia) (Vieira et al, 2007;Vieira et al, 2009;Ferreira et al, 2010;Almeida et al, 2016) diluída em 1 mL de água filtrada, por gavagem (figura 1A), durante 5 dias antes do procedimento cirúrgico.…”
Section: Suplementação Com Creatinaunclassified